Individuals, work, and coercion: A philosophical critique of freedom, creativity, and property in a commodity economy - Chien, Dinh Van; Minh, Nguyen Thanh; Quoc, Nguyen Anh (Edelweiss Applied Science and Technology, 2025)
This article aims to systematically criticize forced individual work in the modern commodity economy, thereby re-discussing the nature of free work, creativity, and ownership in human life. The author raises the question: When work is no longer a manifestation of human nature but becomes a tool to serve money, fame, and social norms, can individuals still live as free, creative, and responsible subjects? Using the method of systemic philosophy combined with sociological criticism, the article examines the relationship between individuals, work, means of production, products, and spiritual life—thereby pointing out the mechanism of "ownership of others" as a typical form of coercion in modern society. The analysis is deployed in an interdisciplinary framework that includes human philosophy, existentialism, sociology, political economy, and sociobiology, helping to clarify the forms of coercion from material to spiritual. The research results show that coercion is no longer limited to industrial work but has penetrated emotional, sexual, moral, and linguistic relationships. Individuals are turned into tools in the exchange system, where the value of life is replaced by price. From there, the article emphasizes that work—if not associated with freedom and creativity—will lead to the loss of human identity. In conclusion, the article affirms that only by restoring the creative nature and intrinsic value of work can individuals overcome coercion and realize freedom as an actual condition of life in modern society.